Exploring a competency framework for the chief financial officer of a hospital: a qualitative study from China - Hongzhi Wang; Xin Xiang; Luping Dong (BMC, 2023)
Abstract Background Hospital chief financial officer (CFO) plays a vital role in supporting the effective management of organization. Understanding their competencies is essential to improve hospital development and health care services in China. This paper aims to explore competencies necessary for hospital CFOs to fulfil their management responsibilities and develop a competency framework for hospital CFOs in China. Methods A qualitative study was applied by conducting in-depth interviews with 151 participants from 15 Chinese provinces, comprising 89 individuals from 67 hospitals, and 62 individuals from 39 medical universities. Interviews were anonymised, recorded and transcribed. Qualitative thematic analysis was applied through a multi-stage review process and modified via the Delphi process using a national panel of 36 experts. Results Using content analysis, we identified 17 competencies organized into three themes (personal attitudes, leadership competencies and managerial competencies) to conduct a competency framework for hospital CFO to fulfil their management practices. Those competencies emphasized the integration of different competencies required by the hospital CFO. Conclusions This paper identified the detailed expertise, abilities and personal traits required by hospital CFOs in China, expanding the insights and perspectives of hospital CFOs currently working in China to literature. The proposed framework will help hospitals establish selection criteria, coaching tools, and development plans for CFOs.